Bookkeeping Training for Ceramic Trading UMKM Entrepreneurs - Irawan, Candra (Assoeltan: Indonesian Journal of Community Research and Engagement, 2025)
Micro, Small, and Medium Enterprises (MSMEs) play a vital role in supporting economic growth, absorbing labor, and reducing poverty, yet many entrepreneurs still face challenges in financial management, particularly in bookkeeping practices. This community service program was carried out to respond to the limited capacity of ceramic trading entrepreneurs in Pekanbaru, who often manage their businesses informally without proper financial recording, which hampers decision-making, cost calculation, and access to financial support. The purpose of this program was to improve the knowledge and skills of MSME entrepreneurs in preparing simple bookkeeping records adapted to their business characteristics. The method applied was the Participatory Action Research (PAR) approach, involving socialization, lectures, discussions, and mentoring that enabled participants to directly practice recording daily transactions and compiling basic financial reports such as balance sheets and income statements. The results show that participants were able to separate personal and business finances, record transactions more regularly, and recognize the strategic importance of bookkeeping for business sustainability. The drawn conclusion is that bookkeeping training contributes significantly to increasing financial literacy and competitiveness of MSMEs, although long-term mentoring is still required to strengthen consistency and adoption of digital tools. This program contributes practically by empowering local entrepreneurs and theoretically by affirming the relevance of financial literacy in MSME development.